On hypersurfaces of Lorentzian standard 4-space forms satisfying a biconservativity condition - Firooz Pashaie (Journal of Mahani Mathematical Research, 2023)
In this manuscript, we consider an extended version of biconservativity condition (namely, ${\textrm C}$-biconservativity) on the Riemannian hypersurfaces of Lorentzian standard 4-space forms. This new condition is obtained by substituting the Cheng-Yau operator ${\textrm C}$ instead of the Laplace operator $Δ$. We show that every ${\textrm C}$-biconservative Riemannian hypersurface of a Lorentzian 4-space form with constant mean curvature has constant scalar curvature.